2‐hydroxyisocaproic acid is fungicidal for Candida and Aspergillus species. Issue 4 (11th October 2013) - Sakko, M.; Moore, C.; Novak‐Frazer, L.; Rautemaa, V.; Sorsa, T.; Hietala, P.; Järvinen, A.; Bowyer, P.; Tjäderhane, L.; Rautemaa, R.
Summary The amino acid derivative 2‐hydroxyisocaproic acid (HICA) is a nutritional additive used to increase muscle mass. Low levels can be detected in human plasma as a result of leucine metabolism. It has broad antibacterial activity but its efficacy against pathogenic fungi is not known. The aim was to test the efficacy of HICA against Candida and Aspergillus species. Efficacy of HICA against 19 clinical and reference isolates representing five Candida and three Aspergillus species with variable azole antifungal sensitivity profiles was tested using a microdilution method. The concentrations were 18, 36 and 72 mg ml−1. Growth was determined spectrophotometrically for Candida isolates and by visual inspection for Aspergillus isolates, viability was tested by culture and impact on morphology by microscopy. HICA of 72 mg ml−1 was fungicidal against all Candida and Aspergillus fumigatus and Aspergillus terreus isolates. Lower concentrations were fungistatic. Aspergillus flavus was not inhibited by HICA. HICA inhibited hyphal formation in susceptible Candida albicans and A. fumigatus isolates and affected cell wall integrity. In conclusion, HICA has broad antifungal activity against Candida and Aspergillus at concentrations relevant for topical therapy. As a fungicidal agent with broad‐spectrum bactericidal activity, it may be useful in the topical treatment of multispecies superficial infections.